Whole Exome Sequencing Reveals Compound Heterozygosity for Ethnically Distinct PEX7 Mutations Responsible for Rhizomelic Chondrodysplasia Punctata, Type 1 - Jessie C. Jacobsen; Emma Glamuzina; Juliet Taylor; Brendan Swan; Shona Handisides; Callum Wilson; Michael Fietz; Tessa van Dijk; Bart Appelhof; Rosamund Hill; Rosemary Marks; Donald R. Love; et al. (Case Reports in Genetics)
We describe two brothers who presented at birth with bone growth abnormalities, followed by development of increasingly severe intellectual and physical disability, growth restriction, epilepsy, and cerebellar and brain stem atrophy, but normal ocular phenotypes. Case 1 died at 19 years of age due to chronic respiratory illnesses without a unifying diagnosis. The brother remains alive but severely disabled at 19 years of age. Whole exome sequencing identified compound heterozygous stop mutations in the peroxisome biogenesis factor 7 gene in both individuals. Mutations in this gene cause rhizomelic chondrodysplasia punctata, type 1 (RCDP1). One mutation, p.Arg232∗, has only been documented once before in a Japanese family, which is of interest given these two boys are of European descent. The other mutation, p.Leu292∗, is found in approximately 50% of RCDP1 patients. These are the first cases of RCDP1 that describe the coinheritance of the p.Arg232∗ and p.Leu292∗ mutations and demonstrate the utility of WES in cases with unclear diagnoses.